The treatment of paediatric burns with concentrated surfactant gel technology: a case series. (1st June 2020) - Pittinger, Timothy P; Curran, Danielle; Hermans, Michel HE
Abstract : Objective: To assess the safety and efficacy of a surfactant-based technology for the management of burns. Method: In a retrospective review, paediatric patients with different types of burns were treated with the gel technology. In some patients, the treatment was combined with a topical antimicrobial agent. Primary objectives of the review were the assessment of healing, healing times and ease of use of the material. Results: The wounds of 15 paediatric patients with different types of burns, particularly with regard to depth and anatomical location, were evaluated using a retrospective chart review. It was found that the surfactant gel technology, with or without the topical antimicrobial agent, assisted in autolytic debridement, and that time to re-epithelialisation was short and within the range of those obtained with other established treatments. Conclusion: The number of patients and wounds in this evaluation is small but the study indicates that the gel technology provides a safe and effective way to treat smaller burns in paediatric patients.